EFFECTS OF TEMPERATURE-pH ON LIQUID PHASE MASS TRANSFER AND DIFFUSION COEFFICIENTS AT LEACHATE TREATMENT IN ANAEROBIC BIOREACTOR - Abdul Kahar; IDAA Warmadewanthi; Joni Hermana (Universitas Lambung Mangkurat, 2018)
Abstract - Leachate contains complex dissolved organic and inorganic substrates that are biodegradable and non-biodegradable. Principally, anaerobic treatment utilizes anaerobic bacteria to degrade the dissolved organic matters. Anaerobic treatment is very sensitive towards the change of temperature and pH. This research used an anaerobic bioreactor with volume of 160L, with a ratio of leachate:biogas was 70:30. Seeding, acclimatization and leachate treatment were executed at temperature 35°C; pH ambient, temperature 45°C; pH ambient, temperature 35°C; pH 7.2 and temperature 45°C; pH 8.0. Based on this research, that there is dependency on mass of solutes organic substrate (COD) in the leachate, at all operating conditions of leachate treatment in anaerobic bioreactor. Hence, the organic substrate concentration (COD) will affect the VFA, the liquid phase mass transfer and diffusion of solute organic. Consequently, the higher the temperature-pH, the higher the liquid-phase mass transfer, but lower diffusion coefficients is. Keywords: anaerobic bioreactor, diffusion, leachate, liquid-phase mass transfer